CONCEPTION RATES AND SEX CONCOMITANT OF BALI CALVES FOLLOWING OESTRUS SYNCHRONIZATION AND ARTIFICIAL INSEMINATION OF FROZEN- SEXED SEMEN UNDER FARM CONDITIONS - Said, S.; Arman, C.; Tappa, B. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
The objective of this study was to determine the conception rate of Bali cattle synchronized andartificially inseminated with frozen thawed sexed-semen concomitant with its calves sex. Thisexperiment was conducted in two cattle farms in West Lombok Regency. Oestrus was synchronized witha single injection i.m. of 5 cc Lutalyse ® containing 25 mg of PGF 2α (Lutalyse, Sterile Solution,Pharmacia Animal Health). The observation was conducted in the responded cattle that artificiallyinseminated at once oestrus. Pregnancy diagnosis was conducted by rectal palpation at about day-90. InFarm 1, the conception rate (CR) of PGF 2α -treated and non-treated animals were 29/63 (46.03%) and71/75 (94.66%), respectively. However, in Farm 2 the corresponding values were 38/89 (42.70%) and10/23 (43.48%), respectively. CR in both farms were found being 100%. Sex concomitant rate forfemale calves born in Farm 1 was found being 94/100 (94.00%), whilst in Farm 2, sex concomitant ratefor male calves born was recorded to be 45/48 (93.75%). It was concluded that under farm conditionsoestrus synchronization using PGF 2α in conjunction with AI of frozen-thawed Bali sexed spermatozoamight be used with acceptable conception and calving rates that above 90 % concomitant with itsrespective calve-sex rates.